What to teach besides science and technology - Vicente Gomes (6854393) (2025)
14/07/2025: Updated author fields 19/06/2025: Updated author, title, and recommended citation fields Mission Atlantic integrated ecosystem assessments E-learning series. This video presents a philosophical approach to exploring the broader utility of IEAs. It takes a step back to critically examine efforts to describe and manage the natural world by considering the diversity of experiences and expertise.